Penggunaan Model Project Based Learning (PjBL) Berbasis Socio- Scientific Issue Untuk Meningkatkan Hasil Belajar Mahasiswa Dalam Mata Kuliah Psikologi Pendidikan - Kurniasari, Praharisti; Mardikaningsihi, Agusti; Aini, Risa Nur (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
The purpose of this study is to improve the learning outcomes of Insan Budi Utomo University students in educational psychology courses through the use of the Problem Based Learning (PjBL) model based on Socio-Scientific Issue. The research method uses classroom action research consisting of 2 cycles. The implementation of Classroom Action Research (PTK) at Insan Budi Utomo University, involved 25 students in the 4th semester of class C in the 2023/2024 intake. Data collection through interviews, observations, and distribution of peer assessment questionnaires. Each cycle consists of Planning, Implementation, Observation and Reflection. The results of this study show a significant increase in Student Learning Outcomes after the use of the Project Based Learning (PjBL) model based on Socio-Scientific Issue, especially in the Educational Psychology course. The increase in student learning outcomes, namely in the Pre-cycle, student learning completeness was 20% then increased significantly by 72% in Cycle I and increased again in Cycle II by 100% student learning completeness. However, in this study the researcher faced several obstacles that affected the effectiveness of the lecture, such as difficulties in using QR code technology and internet connections on campus that were sometimes slow. The solution that the researcher did was to display the video offline and include a QR code on the projector screen as an alternative.